2023
DOI: 10.3390/plants12142649
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Forms of Sulfur on Soil Organic Matter Fractions and Microorganisms in a Pot Experiment with Perennial Ryegrass (Lolium perenne L.)

Elżbieta G. Magnucka,
Grzegorz Kulczycki,
Małgorzata P. Oksińska
et al.

Abstract: This article focuses on the agronomic evaluation of the supplementation of mineral NPKMg fertilizers with elemental sulfur, magnesium, potassium, or ammonium sulfates in pot experiments with ryegrass growing in a sandy Arenosol with very low sulfur content. A benefit evaluation was carried out on the basis of biomass production, crop nutritional status, and changes in the content of soil organic matter fractions. Furthermore, the total number of bacteria, nitrogen-fixing bacteria, and fungi was estimated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 100 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…As for root biomass the MgSO4 treatments obtained significant increases in root weight, where 200 MgSO4 showed the highest value than the other Mg sources and the control treatment, with a 400% biomass increase (Figure 1C). Besides its role in plant defense against ROS, S is important in N uptake and an essential component of amino acids promoting plant and root growth (Mengel and Kirby, 2000;Magnucka et al, 2023). In general, crop growth rate is modified by nitrogen application, and its use can be highly dependent on the supply of Mg and S to plants (Karooki et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…As for root biomass the MgSO4 treatments obtained significant increases in root weight, where 200 MgSO4 showed the highest value than the other Mg sources and the control treatment, with a 400% biomass increase (Figure 1C). Besides its role in plant defense against ROS, S is important in N uptake and an essential component of amino acids promoting plant and root growth (Mengel and Kirby, 2000;Magnucka et al, 2023). In general, crop growth rate is modified by nitrogen application, and its use can be highly dependent on the supply of Mg and S to plants (Karooki et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Some examples where micronutrient levels may or can cause enrichment or depletion of specific microbial groups include microbes involved in S transformations, nitrifying organisms, and N 2 ‐fixers 139 , 140 , 141 . S is an essential component of a number of biomolecules including proteins, vitamins, hormones, and lipids for the generation and conservation of biochemical energy 142 .…”
Section: Attributes/environmental Variables–with Perceived Mechanisti...mentioning
confidence: 99%
“…In turn, soil microbial activity is dependent on temperature, moisture, pH, and substrate availability [51][52][53]. Ikoyi et al [54] found that short-term sulfate fertilization promotes perennial ryegrass growth by outweighing negative feedback from some of the soil biota, while Magnucka et al [55] found that the application of sulfur fertilizers with the mineral NPKMg promotes soil fertility due to aggregate stabilization and a decrease in water-soluble organic compounds. Nitrogen mineralization from soil organic matter can occur more rapidly compared to the release of sulfur [56,57].…”
Section: Soil Properties After Experimentsmentioning
confidence: 99%